Extrato etanólico do caroço da manga na alimentação de frangos de corte - Farias, Nadja Naiara Pereira (2017)
The experiment was carried out to evaluate the effect of inclusion of different levels of ethanolic extract of mango seed (EEMS) on performance, carcass traits, development of the digestive tract and blood parameters of broilers. For this purpose, 756 one-day-old male chicks of the Ross 308 line were distributed in a completely randomized experimental design with seven treatments and six replicates of eighteen birds. The treatments consisted of: ration without addition of antioxidant (control); With addition of 200 ppm of the antioxidant Butylated hydroxytoluene (BHT); And ration with 200, 400, 600, 800 or 1000 ppm of ethanolic extract of the mango seed. There was no significant difference between the treatments for the performance variables, carcass characteristics, as well as for the development of the digestive tract of the broilers. Regarding the serum lipid profile of broiler chickens, it was observed that broiler chickens fed the control ration had significantly higher total cholesterol levels than the animals that received rations containing EEMS. However, there was no significant difference between the use of synthetic antioxidant BHT and the addition of EEMS at different levels. The ethanolic extract of the mango seed can be used to feed broiler chickens from 1 to 42 days of age at levels of up to 1000 ppm of inclusion, without alterations in performance, carcass characteristics, development of the digestive tract and biochemical parameters. However, it influences the lipid metabolism of broilers, reducing total plasma cholesterol.